2021
DOI: 10.1177/11782234211050727
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Cytochrome P450 1A1 and 1B1 Genes in a Cohort of Patients from Iraq Diagnosed with Breast Cancer

Abstract: Breast cancer is the most prevalent malignant neoplasm in females. Genetic variations in the xenobiotic metabolising cytochrome enzymes; Family 1 Subfamily A Member 1 (CYP1A1) and Family 1 Subfamily B Member 1 (CYP1B1) might play a role in the individual susceptibility to breast cancer and its prognosis. The goal of this study is to estimate the incidence of single nucleotide polymorphisms (SNPs) in CYP1A1 (rs1048943, Ile462VaI, and rs4646903/MSP1) and in CYP1B1 (rs1056836, Leu432Val) genes in patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Various studies have shown the significance of CYP 450 polymorphism in the susceptibility to cancer. In hormone-related cancers such as breast cancer ( 53 ) and prostate cancer ( 54 ), CYP 450, which is involved in steroid hormone metabolism, affects cancer susceptibility. Studies have shown that patients carrying a mutation of the CYP1A1/2, CYP2D6, and CYP2E1 have an increased risk of head and neck squamous cell carcinoma, esophageal carcinoma, and lung carcinoma, arising from a deficiency in metabolizing carcinogens to their inactive derivatives ( 55 , 56 ); alcohol and nicotine are common carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the significance of CYP 450 polymorphism in the susceptibility to cancer. In hormone-related cancers such as breast cancer ( 53 ) and prostate cancer ( 54 ), CYP 450, which is involved in steroid hormone metabolism, affects cancer susceptibility. Studies have shown that patients carrying a mutation of the CYP1A1/2, CYP2D6, and CYP2E1 have an increased risk of head and neck squamous cell carcinoma, esophageal carcinoma, and lung carcinoma, arising from a deficiency in metabolizing carcinogens to their inactive derivatives ( 55 , 56 ); alcohol and nicotine are common carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the proportion of the variant genotype CC of rs4646903 with breast cancer stage was reported in contrast to no significant association between genetic polymorphisms of rs4646903 and breast cancer in East Asian, Caucasian, or African populations [31]. A study showed no association between the variant genotypes TC and CC and breast cancer, stage, grade, or molecular sub-type in Iraqi women diagnosed with breast cancer [28]. A study on a southern Indian population indicated a positive association of the variant genotypes TT and TC with breast cancer [13] where a 5-fold association of rs4646903 variant genotype CC supports the role of CYP1A1 in breast cancer susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…The three genotypes were TT (wild type), TC (variant heterozygous) and CC (variant homozygous) [26]. The MspI restriction enzyme identifies the CYP1A1 (rs4646903) polymorphism in the non-coding region of the gene [28].…”
Section: Discussionmentioning
confidence: 99%